Impact of Coconut Water (Cocos Nucifera L) on Total Cholesterol Levels of Patients with Hypercholesterol - Djafar, Ida Ida; Zurimi, Suardi; Rasako, Hairudin; Nendissa, Mintje Maria (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2025)
High levels of cholesterol in the blood increase the risk of atherosclerosis resulting in lipid plaque formation, especially with increased levels of low-density lipoprotein (LDL-C). This study was conducted to determine the impact of coconut water (Cocos nucifera L.) on total cholesterol levels of hypercholesterolemia patients. This type of research is a quasi-experiment. The design used is one group pretest-posttest design, which is research using the same group. Measurements were taken twice before the intervention and after the intervention. The research was conducted in the working area of the Hative Kecil Health Center, Ambon City in September - November 2024. The number of samples was 6 respondents. The pretest research variable shows the mean value obtained is 220.5 mg/dl, the maximum value is 243 mg/dl, the minimum value is 206 and the std. deviation value is 14.7. The posttest variable shows the mean value obtained of 203.8 mg/dl, the maximum value of 238 mg/dl, the minimum value of 183 mg/dl and the std. deviation value of 20.1. The results of the Paired t-Test test, it is known that the significance number shows a value of p = 0.003 < α = 0.05, which means that there is an effect of giving young coconut water (cocos nucifera l.) on total cholesterol levels. Keywords: total cholesterol; cocos nucifera L.water